ACTION RESEARCH AS A DIDACTIC STRATEGY AND CONFLICT RESOLUTION IN THE CLASSROOM - SANCHEZ-GARCIA, Tula (2024)
The present research is a quantitative approach with a descriptive design and was carried out with the students of the Initial Education specialty of the Faculty of Education of UNMSM, in the situational diagnosis motivated to provide possible solutions to the problem, the students observed that there are distractors that interfered in learning for different reasons, they develop the action plan with the objective of resolving conflicts in the classroom in a specific period, at the end of it they presented a report with the results obtained, which is an academic experience where They strengthened teaching skills for the future exercise of their profession. School coexistence presents various scenarios. Conflicts in the classroom occur for any reason or circumstance, which requires attention because they are a distraction and can cause negative emotional states in children under 5 years of age. It is demonstrated that action research as a teaching strategy has positive effects on conflict resolution in the classroom, according to the perception of the students of the X cycle of the Initial Education specialty of the Faculty of Education of the Universidad Nacional Mayor de San Marcos in the 2023-II semester.